Features of the functional state of athletes in various high-performance sports - Kogan, O.S.; Galiullina, S.D.; Gerasimova, D.I.; Safina, E.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to identify the functional state of athletes in various sports, characterising adaptation to increased physical and psycho-emotional overloads and to social environmental factors. Methods and structure of the study. An analysis was carried out of the features of the professional sporting activity of representatives of various sports, based on the analysis of certain psychophysiological indicators in the inter-competitive period. For this purpose, the standard Lüscher and Cattell methods and the Ehlers questionnaire were used. Results and conclusions. The study of the functional state of athletes in terms of indicators of anxiety, conflict and tension revealed their predominance in athletes of complex-coordination sports. High performance indicators have been established in representatives of game sports. The athletes of the martial arts group exhibited a higher motivation to achieve success.